2017
DOI: 10.1111/jwas.12442
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Assessment of a Red Drum, Sciaenops ocellatus, Stock Enhancement Program

Abstract: The South Carolina Department of Natural Resources began a stock enhancement research program for red drum, Sciaenops ocellatus, as a possible management strategy for augmenting the availability of juveniles for recreational harvest in South Carolina estuaries. Between 1999 and 2011, approximately 6 million juveniles and 260 million larvae were stocked into the Charleston Harbor (CH) estuary, and proportions of stocked fish were found through standardized sampling as high as 49.6% within a subadult year‐class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Approximately six million juvenile red drum (20–147 mm mean total length) and 260 million larvae were stocked into Charleston Harbor, South Carolina, USA from 1999 to 2011. Contributions of stocked fish were found to be as high as 49.6% to a single year class within the estuary and exhibited an overall contribution of 3.3% to the spawning population offshore (Katalinas et al., ). In addition, tag–recapture data demonstrated that 95% of juveniles were recaptured within 15 km of their initial tagging location (Arnott et al., ), and individuals stocked into the Charleston Harbor estuary exhibited highly localised contributions (2.5%) to the spawning population just offshore with a contribution no >0.3% to neighbouring estuaries (Gerhard, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately six million juvenile red drum (20–147 mm mean total length) and 260 million larvae were stocked into Charleston Harbor, South Carolina, USA from 1999 to 2011. Contributions of stocked fish were found to be as high as 49.6% to a single year class within the estuary and exhibited an overall contribution of 3.3% to the spawning population offshore (Katalinas et al., ). In addition, tag–recapture data demonstrated that 95% of juveniles were recaptured within 15 km of their initial tagging location (Arnott et al., ), and individuals stocked into the Charleston Harbor estuary exhibited highly localised contributions (2.5%) to the spawning population just offshore with a contribution no >0.3% to neighbouring estuaries (Gerhard, ).…”
Section: Methodsmentioning
confidence: 99%
“…Red drum are managed as two genetically distinct stocks along the United States’ Atlantic coast, with the stock boundary defined at the North and South Carolina border (SEDAR [Southeast Data Assessment and Review], ).This study followed the more conservative approach of Katalinas et al. () by using stocking data specific to the Charleston Harbor estuary because stocked fish made a greater local contribution to the spawning population offshore, and so any genetic influences of stocking primarily would occur within this region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Texas red drum enhancement programme replaces ~25% of the broodfish with wild each year; nevertheless, the analysis suggested a potential R‐L effect (Gold, Ma, Saillant, Silva, & Vega, ; Karlsson, Saillant, Bumguardner, Vega, & Gold, ). In contrast, no effect on genetic diversity was reported in the stocked red drum population in the South Carolina (Katalinas, Brenkert, Darden, & Denson, ). A series of studies on Japanese red sea bream found a panmictic population in western Japan, but there were differences in allele frequencies in KB (Taniguchi & Sugama, ) and Kochi Bay (Perez‐Enriquez, Takemura, Tabata, & Taniguchi, ) populations, and they suggested that these effects might be caused by hatchery releases.…”
Section: Genetic Effects Of Hatchery Propagationmentioning
confidence: 97%